Kết quả nghiên cứu công nghệ xử lý nhiệt Saphir miền Nam Việt Nam - Khôi, Nguyễn Ngọc; Long, Phạm Văn (Vietnam Journal of Earth Sciences, 2009)
Some results of study on the technology for heat treatment of South Vietnam sapphires ...